Validation of the CHADS2 clinical prediction rule to predict ischaemic stroke - Keogh, Claire; Wallace, Emma; Dillon, Ciara; Dimitrov, Borislav D.; Fahey, Tom (Thrombosis and Haemostasis, 2011)
The CHADS2 predicts annual risk of ischaemic stroke in non-valvular atrial fibrillation. This systematic review and meta-analysis aims to determine the predictive value of CHADS2. The literature was systematically searched from 2001 to October 2010. Data was pooled and analysed using discrimination and calibration statistical measures, using a random effects model. Eight data sets (n=2815) were included. The diagnostic accuracy suggested a cut-point of ≥1 has higher sensitivity (92%) than specificity (12%) and a cut-point of ≥4 has higher specificity (96%) than sensitivity (33%). Lower summary estimates were observed for cut-points ≥2 (sensitivity 79%, specificity 42%) and ≥3 (specificity 77%, sensitivity 50%). There was insufficient data to analyse cut-points ≥5 or ≥6. Moderate pooled c statistic values were identified for the classic (0.63, 95% CI 0.52–0.75) and revised (0.60, 95% CI 0.43–0.72) view of stratification of the CHADS2 . Calibration analysis in-dicated no significant difference between the predicted and observed strokes across the three risk strata for the classic or revised view. All results were associated with high heterogeneity, and conclusions should be made cautiously. In conclusion, the pooled c statistic and calibration analysis suggests minimal clinical utility of both the classic and revised view of the CHADS2 in predicting ischaemic stroke across all risk strata. Due to high heterogeneity across studies and low event rates across all risk strata, the results should be interpreted cautiously. Further validation of CHADS2 should perhaps be undertaken, given the methodological differences between many of the available validation studies and the original CHADS2 derivation study.
Keywords: Atrial fibrillation; cerebral infarct; risk factors; risk prediction; CHADS2